Evaluating the effectiveness of different cartographic design variants for influencing route choice. Issue 2 (4th March 2021) - Fuest, Stefan; Grüner, Susanne; Vollrath, Mark; Sester, Monika
ABSTRACT: This paper addresses the suitability of different cartographic design variants for visually communicating recommended routes. We performed a user study, investigating the potential of six different design variants ( color hue, distortion, length distortion, size, spacing, and symbols ) for influencing route choice using cartographic visualization methods while recommending a longer, but less congested route. The visualizations for all design variants have been prepared in three different levels of intensity of modification ( weak, medium, and strong ). Although the input data (traffic density) is the same for all representation methods, variations are each visualized using different cartographic design principles. Our results showed that in general, for the majority of routing scenarios, the participants' route choice has been significantly influenced toward choosing the recommended route – indicating that the modification of route visualizations does actually lead to a different route choice behavior. Results further revealed that for most variants, willingness to choose the recommended route increases with higher intensity of modification. While some of the design variants like symbols or length distortion have been found effective for recommending routes at all levels of intensity, others like size and spacing have not been found suitable. A comparison between route choices and estimated route characteristics suggested a close relationship between willingness to choose the recommended route and the characteristics participants associate with the representation. In particular, route visualizations that create an impression of faster, more convenient, or more fluent travel experience are more likely to influence route choice behavior.